Melomys cervinipes (Rodentia: Muridae). (3rd October 2018) - Callaway, Wendy A; Turner, Ayla A; Croshaw, Oscar B; Ferguson, Jade A; Julson, Zachary J -N; Volp, Trevor M; Kerr, Sarah E; Rymer, Tasmin L
Abstract: Melomys cervinipes (Gould, 1852) is a murid rodent commonly called the fawn-footed mosaic-tailed rat. A small, russet brown rodent with light fawn-colored feet, it is 1 of 21 currently recognized species in the genus Melomys . The species is endemic to Australia, occurring in the rainforests and forests along the eastern coast. M. cervinipes is listed as "Least Concern" by the International Union for the Conservation of Nature and Natural Resources.